Thoracoscopic Surgery for Posterior Mediastinal Mass: Our Initial Experience - Sapkota, Ranjan; Sayami, Prakash (Journal of College of Medical Sciences-Nepal, 2019)
Background: Thoracoscopic surgery has been increasingly used for a variety of indications. Posterior mediastinal tumors form an important component of a thoracic surgeon’s workload. This report represents a summary of our initial experience in thoracoscopic management of such tumors. Methods: We retrospectively reviewed the clinical and operative data from records over the study period. We also describe our usual perioperative management and surgical techniques. Results: A total of 11 patients, 8 being females, were operated during the period of 30 months. Seven were incidental findings, and chest pain was the commonest presentation in symptomatic patients. The mean age of the patients was 38.7 years; mean tumor diameter was 4.4 cm; eight had benign schwannoma, and no patient had a malignant tumor. Mean operative duration was 175.5 min; there were no conversions and no transfusion was required. Mean length of stay in the hospital was 5.6 days. There were no perioperative deaths or major complications. Three minor complications were recorded. Follow-up (4 to 18 months) was uneventful. Conclusions: Thoracoscopic management of posterior mediastinal tumors is feasible and safe.